Is a diagnostic lumbar puncture indicated in intraocular retinoblastoma? - Sidharth Totadri; Vinay Munikoty; Usha Singh; Radhika Srinivasan; Amita Trehan; Richa Jain; Nandita Kakkar; Akshay Kumar Saxena; Arvind Rajwanshi; Deepak Bansal (Wolters Kluwer Medknow Publications, 2018)
Background: Lumbar puncture (LP) is frequently performed in patients with advanced intraocular retinoblastoma. However, this may not be necessary in a significant proportion of patients. Materials and Methods: A file review of patients who were diagnosed with retinoblastoma over a 13-year-period was performed. Patients who underwent LP as part of staging were included in the study. Results: The study included 223 patients. One-third had bilateral retinoblastoma. The grouping was C, D, and E in 4 (2.9%), 41 (29.9%), and 92 (67.2%) patients, respectively. The stage was 0, I, II, III, and IV in 14 (6.3), 123 (55.2%), 13 (5.8%), 70 (31.4%), and 3 (1.3%) patients, respectively. Eight (3.6%) patients had a positive cerebrospinal fluid (CSF) cytology. None of the patients with intraocular disease and 7 (10%) patients with extraocular disease had a positive CSF. Conclusions: A diagnostic CSF is not indicated in patients with intraocular retinoblastoma.